Seasonal cyclical changes in the gonadal activity of common carp, Cyprinus carpio Linn - Guha, Dhriti; Mukherjee, Dilip (Indian Journal of Fisheries, 2011)
Annual reproductive cycle includingcyclic changes in ovarian and testicular activityhave been studied in several teleosts inrelation to their environmental regulation(Billardef fl/. 1978, Peter and Crim 1979, Lam1983, Scott and Sumpter 1983, Kaneko andHanyu 1985, Mukhopadhyay and Sinha1986). Common ceap, Cyprinus carpio, is anextensively cultivated species with 2 breedingperiods, one during mid January to Februaryand other during July to August (Alikunhi1966, Jhingran 1985)